Efektivitas Range of Motion (ROM) Terhadap Fungsional Dan Kualitas Hidup Lansia: A Literature Review - Gustina, Nurma Zela (Media Literasi Indonesia, 2026)
Background: Older adults in nursing homes face a significant risk of joint contractures and functional decline due to limited mobility, which ultimately diminishes their quality of life. Range of Motion (ROM) exercises serve as a vital non-pharmacological intervention to address these issues. Objective: This systematic literature review aims to synthesize empirical evidence regarding the effectiveness of ROM exercises on the functional capacity and quality of life of institutionalized older adults. Methods: Following PRISMA guidelines, a structured search was conducted in the Scopus database for publications between 2022 and 2024. Ten studies met the inclusion criteria and were synthesized. Results: The review indicates that structured ROM programs, particularly active ROM, significantly improve joint flexibility, muscle strength, and functional independence (ADL). Furthermore, ROM exercises promote mental well-being by reducing anxiety and increasing self-control. However, challenges such as limited skilled staff and low resident motivation remain significant barriers. Conclusion: ROM is a practical, low-risk strategy that effectively preserves functional independence and enhances the overall quality of life for older adults in nursing homes.